Os tipos das plantas vasculares do herbário da Universidade Federal de Viçosa (VIC): III - Piperaceae - Rodrigues Vidal, Maria Rosária; Nunes Vidal, Waldomiro (Revista Ceres, 2025)
This paper consists of a selection of types of the Piperaceae, from the Viçosa herbarium (VIC). Transcriptions ofthe original descriptions were made, thereby attempting to establishthe categories of the types exis- ting in the herbarium.